MAP VERSUS TEXT: ON CHALLENGES WHILE DESIGNING A CARTOGRAPHIC REPRESENTATION OF "BLACK TORRENT" - Gołębiowska, Izabela; Korycka-Skorupa, Jolanta (Prace Polonistyczne, 2024)
A map communicates information in a symbolic, visual way. It is informed by mathematical calculations which guarantee correctness and precision of spatial representation. It is therefore a challenge to show the content of a verbal description as a map. The cartographic methodology poses many restrictions and requirements regarding the mapped data, which are not applicable to a verbal description. The essential differences between verbal and cartographic forms of communication were a challenge while designing a map of Black Torrent. Thus, the article discusses the challenges related to translating the text of Leopold Buczkowski’s novel into the language of a map in accordance with the principles of cartographic and graphic design of thematic maps.